2015
DOI: 10.1109/rita.2015.2418011
|View full text |Cite
|
Sign up to set email alerts
|

Creation of Customized Remote Laboratories Using Deconstruction

Abstract: The employment of customized remote laboratories becomes very relevant for the teaching community in distance education, since lecturers have the necessity to use real equipment through the Internet, which is adapted to the students' skills. In addition to this, the creation and publication of utilities as services (being infrastructure as a service, platform as a service, or software as a service) have been a hot topic in recent years. This paper describes how the adaptation of real scientific laboratories ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In these studies, the concept of Laboratory as a Service (LaaS), representing resources as sets of services, is studied. Flexible configurations of remote can be performed [16,17]. Laboratories can be easily developed using this technique within a virtual course.…”
Section: Virtualization Of Remote Laboratoriesmentioning
confidence: 99%
“…In these studies, the concept of Laboratory as a Service (LaaS), representing resources as sets of services, is studied. Flexible configurations of remote can be performed [16,17]. Laboratories can be easily developed using this technique within a virtual course.…”
Section: Virtualization Of Remote Laboratoriesmentioning
confidence: 99%
“…Recently, low-cost remote laboratories have been developed for renewable energies (wind and solar) [5]. These resources can be seen as a set of services (Laboratory as a Service, LaaS) which allow the flexible configuration of remote laboratories within a virtual course [6]. Regarding this field of study, other examples of remote laboratories for real renewable energies can be found in the literature, such as [7,8].…”
Section: State Of the Artmentioning
confidence: 99%
“…More details about the deconstruction of remote laboratories can be found in [2]. The creation of LaaS involves three steps.…”
Section: Laboratories As a Service (Laas) Proposalmentioning
confidence: 99%
“…This way, the same laboratory can be adapted to the needs of its users, increasing its versatility. As an example, remote laboratories as a set of services for renewable energies have been developed [2].…”
Section: Introductionmentioning
confidence: 99%